The Effect of Product Innovation, Product Creativity and Product Quality on Superiority Competing on Suputra Herbal Incense in Badung Regency - Gusti Ayu Made Dessy Agrantini; Ade Maharini Adiandari (Baca Dulu Publisher, 2024)
In Indonesia, one sector that is starting to be of interest is the creative economy sector. The creative economy uses renewable resources that are abundant in Indonesia by increasing innovation, creativity and product quality so that they have a higher selling value. Companies must be able to understand consumers and their desires and divide the market into segments or groups of consumers and determine the desires of each of these segments. This research was conducted with the aim of knowing the Effect of Product Innovation, Product Creativity and Product Quality on Competitive Advantage in Suputra Herbal Incense. The population used in this study were all consumers of Herbal Incense for Suputra Herbal Incense in 2020-2021, totaling 110 consumers. The sampling method in this study used simple random sampling with a total sample of 86 respondents. The data analysis techniques used in this study are validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Product Creativity is positive and significant to Competitive Advantage. Product Quality has a positive and significant effect on Competitive Advantage. The magnitude of the influence of the independent variables on Competitive Advantage Seeing the results of Competitive Advantage, Suputra Herbal Incense's research must complement the existing equipment in the company. Complete equipment will make it easier for employees to work better and faster so that they can create satisfaction for their customers.